Medication monitoring attitudes and perceived determinants to offering medication adherence advice to older hypertensive adults: a factorial survey of community pharmacy interns. (13th June 2018) - Dillon, Paul; Smith, Susan M; Gallagher, Paul; Cousins, Gráinne
Abstract: Introduction: Community pharmacy is an ideal setting to monitor medication adherence, however, barriers to pharmacist-led interventions exist. Preparing future pharmacists for enhanced roles may overcome such barriers. Our objective was to identify medication monitoring attitudes and contextual factors that influence adherence monitoring by pharmacy interns to inform educational activities on medication adherence. Methods: An online factorial survey of all pharmacy interns ( N = 123) in the Republic of Ireland, completing advanced community pharmacy experiential learning in May 2016 was undertaken to evaluate attitudes to medication monitoring and to identify respondent characteristics and contextual factors which influence adherence monitoring of older hypertensive adults during repeat dispensing. The medication monitoring attitude measure (MMAM) was used to evaluate interns' attitudes, and factorial vignette analysis was performed to identify factors influencing behavioural intention to offer adherence advice. Results: There were 121 completed online surveys. Half of interns reported they felt uncomfortable and confrontational discussing adherence with patients. In factorial vignette analysis, higher medication monitoring attitudes resulted in higher likelihood to offer adherence advice; experiential-learning characteristics such as pharmacy ownership-type (nonchain store) and contextual factors including patients being treated for longer and time-pressures had a significant negative influence on pharmacy interns' likelihood to offer adherence advice. Discussion: Medication monitoring attitudes and contextual factors influenced responses to offer adherence advice in hypothetical scenarios. Ensuring pharmacy students are educated on patterns of adherence and appropriate skills to address nonadherence, and engage in structured programmes to facilitate patient interactions during experiential learning, may improve medication monitoring attitudes and adherence monitoring.